EXPLORING STAKEHOLDERS EXPERIENCES AND CHALLENGES ON THE PRINTED MODULAR DISTANCE LEARNING MODALITY AMIDST COVID19 PANDEMIC - Palad, Ingrid A. (Jurnal Aplikasi Manajemen, 2022)
The unprecedented outbreak of novel coronavirus brought disruptions to people's lives. Schools were closed due to the imposed different community quarantine. The Department of Education collaborates with different stakeholders to develop a Basic Learning Continuity Plan. Schools used different learning modalities based on the parent's and students' capacity. The study wants to find out the experiences, challenges or difficulties, and suggestions of five school stakeholders in the province of Quezon. This study used a qualitative method through semi-structured interviews. The researcher found out that training and seminars provided by the department of education to all teachers made them confident in implementing printed modular distance learning modality. Monitoring and evaluating learners' progress are some of the most challenging parts in implementing printed modular distance learning as claimed by the teacher-respondents. Communicating with students and parents is one of the challenges faced by the teachers due to limited internet signals in the area. The majority of the learners do not have gadgets like smartphones and laptops. Collaborations and strong partnerships with parents and colleagues helped the teachers cope with the mentioned challenges. For the parents, the most challenging part was establishing routine among their children in studying. Assistance from relatives, searching the internet and using other learning resources like books and asking for assistance from the teachers help the parents face the challenges they encountered. For the student's they find it hard to study alone the module. Some lesson needs to be explained to them to understand well. Performance tasks were among the student's preferences in implementing printed modular distance learning. Parents' and relatives' assistance helps the learner in doing activities. Using books and other supplementary materials and searching on the internet also help the learners do the activities stated in the modules.